El teletrabajo como desafío para mejorar la movilidad urbana en la Provincia de Pichincha cantones de estudio: Rumiñahui, Mejía y Quito - Vela Mosquera, Maritza Elizabeth (2016)
The obvious problems that arise in the capital of Ecuador, Quito, as well as in neighboring cantons, Mejia and Rumiñahui, on issues related to urban mobility make at the moment the system to collapse and in the future to get worse. It is now common to see transport units traveling at full capacity, but there are still plenty of people requesting for transport. Therefore, urban mobility is no longer a political issue and has become a social problem, which brings collateral consequences to the family economy, productivity of individuals and companies, costs of cities, among other reasons. It is necessary to analyze new working ways to reduce the harmful effects of urban mobility in the current conditions. Under this idea, research in primary and secondary sources let us conceptualize mobility problems and making visible the difficulties associated with the work, leading urgently to change current job practices and making essential to generate spaces that allow to address, among other issues, those related to urban mobility. As outcome of the study, it showed that public institutions have been establishing rules in their own area on issues of redistribution of space, hours of traveling, definition of special routes, etc., which are pure administrative activities. While society requires fast solutions that allow two things: more time to strengthen family and/or social relations and the less use of resources, both monetary and non-monetary. In order to prevent fruitless wear; there are open possibilities to include telework as a challenge to improve urban mobility in cities of study.